Efficacy and tolerability of delapril plus indapamide versus lisinopril plus hydrochlorothiazide combination treatments in mild to moderate hypertension: a multicenter, randomized clinical study - Cremonesi, Giovanni; Cavalieri, Luca; Bacchelli, Stefano; Esposti, Daniela Degli; Cikes, Ivo; Dobovisek, Jurij; Zeman, Jan; Borghi, Claudio; Ambrosioni, Ettore (Current therapeutic research, clinical and experimental, 2003)
BACKGROUND: Several studies have shown that antihypertensive monotherapy is commonly insufficient to control blood pressure (BP) in hypertensive patients and that concomitant use of ≥2 drugs is necessary in ∼50% of these patients. The combination of an angiotensin-converting enzyme (ACE) inhibitor and a diuretic, delapril plus indapamide (D + I), has been shown to be effective and tolerable, with no interaction between the 2 components. Another widely used combination of ACE inhibitor and diuretic is lisinopril plus hydrochlorothiazide (L + H). OBJECTIVES: The aims of this study were to confirm the antihypertensive efficacy and tolerability of the fixed combination of D + I in mild to moderate hypertension, and to compare its therapeutic efficacy and tolerability with that of L + H. METHODS: The antihypertensive efficacy and tolerability of a fixed combination of D + I (30-mg + 2.5-mg tablets once daily) or L + H (20-mg + 12.5-mg tablets once daily) in patients with mild to moderate hypertension were compared in a multinational, multicenter, randomized, 2-armed, parallel-group study. Eligible patients were aged 18 to 75 years and had a diastolic blood pressure (DBP) 95 to 115 mm Hg and a systolic blood pressure (SBP) ≤180 mm Hg, both measured in the sitting position. After a single-blind, placebo run-in period of 2 weeks, patients were randomized to receive 1 of the 2 treatments for a 12-week period. The primary efficacy end point was the BP normalization rate (ie, the percentage of patients with a sitting DBP ≤90 mm Hg) after 12 weeks of treatment. Secondary end points were as follows: (1) the responder rate (ie, the percentage of patients whose sitting DBP was reduced by ≥10 mm Hg from baseline or had a DBP ≤90 mm Hg after 12 weeks of treatment), (2) the percentage of patients with a DBP ≤85 mm Hg, and (3) changes in sitting SBP and DBP after 4, 8, and 12 weeks of treatment. RESULTS: A total of 159 hypertensive patients (88 women, 71 men) were randomized to receive D + I (44 women, 36 men; mean [SD] age, 53 [(11)] years) or L + H (44 women, 35 men; mean [SD] age, 55 [(10)] years). No significant between-group differences were found in any of the primary or secondary end points of the study. Both combinations induced a significant reduction in sitting DBP and SBP from baseline (P<0.001 for both groups at week 12), without significant differences between the groups. Five mild to moderate adverse drug reactions (ADRs) occurred in each treatment group. No patient dropped out of the study because of an ADR. CONCLUSION: This study showed no difference between D + I and L + H interms of antihypertensive efficacy or tolerability in patients with mild to moderate hypertension.
Keywords: hypertension; combination therapy; hydrochlorothiazide; indapamide; delapril; lisinopril